THE EFFECT OF NUMERICAL LITERACY LEARNING MODEL ON THE FIFTH-GRADE STUDENTS’ MATHEMATICS LEARNING OUTCOMES AT SD NEGERI 156320 SIMPANG TIGA 2 - Reno Francius Simanullang; Patri Janson Silaban; Dyan Wulan Sari H.S; Darinda Sofia Tanjung; Juliana Juliana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
This paper describes the effect of applying the numerical literacy learning model on students’ mathematics learning outcomes in the material of collecting and presenting data in class V at SD Negeri 156320 Simpang Tiga 2 in the academic year 2022/2023. The research uses a quantitative research method. The research population is 30 fifth-grade students of SD Negeri 156320 Simpang Tiga 2, which consist of 16 male and 14 female students. The sampling technique uses a purposive sample, which distributes in class V with the number of 30 students. The research results indicate that students’ learning outcomes using the numerical literacy model are considered in the good category with an average score of 77.96 and a correlation test result of 0.983, which means rcount (0.983) ≥ rtable (0.361), hence Ha is accepted. Thus, there is a very strong influence between the use of the numerical literacy learning model on students’ mathematics learning outcomes in the material of collecting and presenting data in class V at SD Negeri 156320 Simpang Tiga 2. It can be seen from the results of the T-test research where tcount 28.266 ≥ ttable 1.697 so that it can be stated that Ha is accepted. It shows that there is a significant positive effect from the use of the numerical literacy learning model on students' mathematics learning outcomes in the material of collecting and presenting data in class V at SD Negeri 156320 Simpang Tiga 2 in the academic year 2022/2023.